Fabrication, properties and in vitro study of Magnesium/ Zinc/ Bioglass composite fabricated by powder metallurgy method - Noorazimah Mohd Ab Llah (School of Materials Engineering, Universiti Malaysia Perlis, 2016)
Objectives of study are to fabricate Mg/3Zn/ bioglass composite using powder metallurgy method; to investigate the effect of bioglass weight percentage and sintering temperature to the Mg/3Zn/ bioglass composite in terms of microstructure, physical properties, mechanical properties, corrosion and bioactivity behavior and ; to characterise the samples by their phase tranformation, microstucture, density, porosity, compressive strength, corrosion rate and appetite formation.